Quantitative Proteomic Analysis Reveals That Arctigenin Alleviates Concanavalin A-Induced Hepatitis Through Suppressing Immune System and Regulating Autophagy - Feng, Qin; Yao, Jingchun; Zhou, Ge; Xia, Wenkai; Lyu, Jingang; Li, Xin; Zhao, Tao; Zhang, Guimin; Zhao, Ningwei; Yang, Jie (Frontiers in Immunology, 2018)
Concanavalin A-induced autoimmune hepatitis is a well-established experimental model for immune-mediated liver injury. It has been widely used in the therapeutic studies of immune hepatitis. The in-depth analysis of dysregulated proteins from comparative proteomic results indicated that the activation of immune system resulted in the deregulation of autophagy. Follow-up studies validated that some immune related proteins, including Stat1, Pkr, Atg7, and Adrm1, were indeed upregulated. The accumulations of LC3B-II and p62 were confirmed by immunohistochemistry and Western blot analyses. Arctigenin pretreatment significantly alleviated the liver injury, as evidenced by biochemical and histopathological investigations, whose protective effects were comparable with Prednisone acetate and Cyclosporin A. Arctigenin pretreatment decreased the levels of IL-6 and IFN-γ, but increased the ones of IL-10. Next, the quantitative proteomic analysis demonstrated that ARC pretreatment suppressed the activation of immune system through the inhibition of IFN-γ signaling, when it downregulated the protein expressions of Stat1, P-Stat1, Pkr, P-Pkr, Bnip3, Beclin1, Atg7, LC3B, Adrm1, and p62. Meanwhile, Arctigenin pretreatment also reduced the gene expressions of Stat1, Pkr, and Atg7. These results suggested that Arctigenin alleviated autophagy as well as apoptosis through inhibiting IFN-γ/IL-6/Stat1 pathway and IL-6/Bnip3 pathway. In summary, the comparative proteomic analysis revealed that the activation of immune system led to Concanavalin A-induced hepatitis. Both autophagy and apoptosis had important clinical implications for the treatment of immune hepatitis. Arctigenin might exert great therapeutic potential in immune-mediated liver injury.